Approach to internal medicine a resource book for clinical practice - Hui, David 1975- (Springer, 2011)
Feedback from users suggest this resource book is more comprehensive and more practical than many others in the market. One of its strengths is that it was written by trainees in internal medicine who understand the need for rapid access to accurate and concise clinical information, with a practical approach to clinical problem solving.